Determinants of Work Participation in Jambi Province: Analysis of Gender and Education Interaction - Adriani, Evi; Fahmi, Ali; Simarmata, Jonner (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Participation in the labor market is a crucial indicator of community involvement in economic development; however, various barriers still hinder individuals from fully engaging in the labor force. Structural factors such as education and gender norms play a significant role in shaping labor force participation patterns. This study aims to analyze the determinants influencing labor force participation in Jambi Province, with a particular focus on the roles of education and gender. Employing a quantitative approach and logistic regression analysis, this research uses data from the 2023 National Labor Force Survey (Sakernas). The findings reveal significant differences in labor force participation between men and women, influenced by educational attainment and marital status. The study also found that women with higher education levels tend to be more active in the labor market, although marriage can be a constraint. These findings are expected to provide insights for policymakers in designing more inclusive programs that empower women and reduce gender disparities in the labor market in Jambi Province.